The Effect of "Police Image" in Hong Kong Gangster Films on the Public’s Perception of Police - Ziheng Zhou (Al-Qanṭara, 2024)
The intricate interplay between the portrayal of Hong Kong police in gangster films and the public's perception of law enforcement signifies a dynamic relationship between entertainment media and societal realities. This study delves into the multifaceted influences that shape public attitudes towards law enforcement in Hong Kong, with a specific focus on media representations, personal experiences, and cultural variables. Conducting semi-structured interviews with 22 Hong Kong residents, this research employed a rigorous three-step coding analysis – encompassing open, axial, and selective coding – to unveil patterns and themes within interview data. The findings reveal a diverse array of factors contributing to public perceptions of law enforcement. Media portrayals, particularly in gangster films, emerged as influential, with positive portrayals correlating with favorable opinions, and negative portrayals leading to more negative attitudes. However, the impact of media was just one facet. Personal interactions with police were pivotal determinants, with positive encounters fostering trust, and negative ones contributing to skepticism. Cultural variables, including age, gender, ethnicity, and socioeconomic status, also played significant roles in shaping attitudes. Cultural values, such as Confucian principles and liberal ideals, underpinned varying perspectives on the police. The practical ramifications of this research include providing legislators and law enforcement agencies with ideas on how to strengthen relations between the police and the community and foster public trust. It also establishes the framework for further research, encouraging investigation into the influence of media on public opinion in various cultural situations. In summary, this study unveils the complex relationship between media, culture, and public perceptions of law enforcement in Hong Kong, providing a nuanced understanding of this intricate interplay.